Value of Echogenic Foci in Diagnosing Papillary Thyroid Carcinoma and Predicting Aggressive Biological Behavior. (20th August 2021) - Wang, Guojuan; Nie, Fang; Wang, Yanfang; Wang, Peihua; Wang, Lan; Fan, Xiao; Ma, Zhenxian
Abstract : Objectives: To assess the diagnostic value of echogenic foci in papillary thyroid carcinoma (PTC) and the relationship between echogenic foci and aggressiveness of PTC. Methods: From January 2018 to January 2021, a total of 950 patients diagnosed with thyroid nodules ( n = 1113) in our hospital were retrospectively analyzed. Among the 1113 nodules, single PTC in 527 patients confirmed by surgery was studied for their aggressive biological behavior. The patterns of echogenic foci were classified as: no echogenic foci, sparse punctate echogenic foci, focal punctate echogenic foci, diffuse punctate echogenic foci, petal‐like punctate echogenic foci, comet‐tail artifacts, coarse echogenic foci, peripheral rim (eggshell echogenic foci), and mixed echogenic foci. The clinical and ultrasonographic characteristics were also analyzed. A univariate analysis was performed, and binary logistic regression was performed to screen independent risk factors. Results: For the differential diagnosis of PTC, age < 50 years, size <1.1 cm, hypoechoic or very hypoechoic, aspect ratio > 1, irregular shape, types II (punctate echogenic foci) and VI (mixed echogenic foci) were independent risk factors. For the aggressive biological behavior of PTC, male sex, age<42 years, size <1.0 cm, types IIb (focal punctate echogenic foci), IIc (diffuse punctate echogenic foci), and VI (mixed echogenic foci) were independent risk factors for predicting cervical lymph node metastasis of PTC. Conclusion: Echogenic foci are useful in diagnosing PTC and predicting aggressiveness of PTC, which contribute to screening invasive PTC and avoiding overdiagnosis and overtreatment.